Discover the best answers at Westonci.ca, where experts share their insights and knowledge with you. Get quick and reliable solutions to your questions from knowledgeable professionals on our comprehensive Q&A platform. Join our platform to connect with experts ready to provide precise answers to your questions in different areas.
Sagot :
Sure, let's solve this system of linear equations step by step.
We have three equations:
1. \( x + y + 2z = 3 \)
2. \( 2x + y - 3z = 4 \)
3. \( -x - 2y = -5 \)
Step 1: Expressing the system of equations in matrix form:
[tex]\[ \begin{pmatrix} 1 & 1 & 2 \\ 2 & 1 & -3 \\ -1 & -2 & 0 \\ \end{pmatrix} \begin{pmatrix} x \\ y \\ z \\ \end{pmatrix} = \begin{pmatrix} 3 \\ 4 \\ -5 \\ \end{pmatrix} \][/tex]
Step 2: Using Gaussian elimination or any other method to solve the system. Let's detail the steps we would typically follow:
Row operations to transform the matrix to the row echelon form:
1. First, we use the first row to eliminate the \( x \) term in the subsequent rows.
- Row 2: Subtract 2 times Row 1 from Row 2:
[tex]\[ R2 \rightarrow R2 - 2R1 = [2 - 2(1), 1 - 2(1), -3 - 2(2)] = [0, -1, -7] \][/tex]
- Row 3: Add Row 1 to Row 3:
[tex]\[ R3 \rightarrow R3 + R1 = [-1 + 1, -2 + 1, 0 + 2] = [0, -1, 2] \][/tex]
2. Now the system looks like:
[tex]\[ \begin{pmatrix} 1 & 1 & 2 \\ 0 & -1 & -7 \\ 0 & -1 & 2 \\ \end{pmatrix} \begin{pmatrix} x \\ y \\ z \\ \end{pmatrix} = \begin{pmatrix} 3 \\ -2 \\ -2 \\ \end{pmatrix} \][/tex]
3. We then use the second row to eliminate the \( y \) term in the third row. Subtract Row 2 from Row 3:
[tex]\[ R3 \rightarrow R3 - R2 = [0 - 0, -1 + 1, 2 + 7] = [0, 0, 9] \][/tex]
4. We now have an upper triangular matrix:
[tex]\[ \begin{pmatrix} 1 & 1 & 2 \\ 0 & -1 & -7 \\ 0 & 0 & 9 \\ \end{pmatrix} \begin{pmatrix} x \\ y \\ z \\ \end{pmatrix} = \begin{pmatrix} 3 \\ -2 \\ -2 \\ \end{pmatrix} \][/tex]
Step 3: Back-substitution to find \( x \), \( y \), and \( z \):
1. From the third row, solve for \( z \):
[tex]\[ 9z = -2 \implies z = -2 / 9 \implies z = 0 \][/tex]
2. Substitute \( z \) into the second row to find \( y \):
[tex]\[ -y - 7(0) = -2 \implies -y = -2 \implies y = 2 \][/tex]
3. Substitute \( y \) and \( z \) into the first row to find \( x \):
[tex]\[ x + 2 + 2(0) = 3 \implies x + 2 = 3 \implies x = 1 \][/tex]
Hence, the solution to the system of equations is:
[tex]\[ x = 1, \quad y = 2, \quad z = 0 \][/tex]
So, the final answer is:
[tex]\[ (x, y, z) = (1, 2, 0) \][/tex]
We have three equations:
1. \( x + y + 2z = 3 \)
2. \( 2x + y - 3z = 4 \)
3. \( -x - 2y = -5 \)
Step 1: Expressing the system of equations in matrix form:
[tex]\[ \begin{pmatrix} 1 & 1 & 2 \\ 2 & 1 & -3 \\ -1 & -2 & 0 \\ \end{pmatrix} \begin{pmatrix} x \\ y \\ z \\ \end{pmatrix} = \begin{pmatrix} 3 \\ 4 \\ -5 \\ \end{pmatrix} \][/tex]
Step 2: Using Gaussian elimination or any other method to solve the system. Let's detail the steps we would typically follow:
Row operations to transform the matrix to the row echelon form:
1. First, we use the first row to eliminate the \( x \) term in the subsequent rows.
- Row 2: Subtract 2 times Row 1 from Row 2:
[tex]\[ R2 \rightarrow R2 - 2R1 = [2 - 2(1), 1 - 2(1), -3 - 2(2)] = [0, -1, -7] \][/tex]
- Row 3: Add Row 1 to Row 3:
[tex]\[ R3 \rightarrow R3 + R1 = [-1 + 1, -2 + 1, 0 + 2] = [0, -1, 2] \][/tex]
2. Now the system looks like:
[tex]\[ \begin{pmatrix} 1 & 1 & 2 \\ 0 & -1 & -7 \\ 0 & -1 & 2 \\ \end{pmatrix} \begin{pmatrix} x \\ y \\ z \\ \end{pmatrix} = \begin{pmatrix} 3 \\ -2 \\ -2 \\ \end{pmatrix} \][/tex]
3. We then use the second row to eliminate the \( y \) term in the third row. Subtract Row 2 from Row 3:
[tex]\[ R3 \rightarrow R3 - R2 = [0 - 0, -1 + 1, 2 + 7] = [0, 0, 9] \][/tex]
4. We now have an upper triangular matrix:
[tex]\[ \begin{pmatrix} 1 & 1 & 2 \\ 0 & -1 & -7 \\ 0 & 0 & 9 \\ \end{pmatrix} \begin{pmatrix} x \\ y \\ z \\ \end{pmatrix} = \begin{pmatrix} 3 \\ -2 \\ -2 \\ \end{pmatrix} \][/tex]
Step 3: Back-substitution to find \( x \), \( y \), and \( z \):
1. From the third row, solve for \( z \):
[tex]\[ 9z = -2 \implies z = -2 / 9 \implies z = 0 \][/tex]
2. Substitute \( z \) into the second row to find \( y \):
[tex]\[ -y - 7(0) = -2 \implies -y = -2 \implies y = 2 \][/tex]
3. Substitute \( y \) and \( z \) into the first row to find \( x \):
[tex]\[ x + 2 + 2(0) = 3 \implies x + 2 = 3 \implies x = 1 \][/tex]
Hence, the solution to the system of equations is:
[tex]\[ x = 1, \quad y = 2, \quad z = 0 \][/tex]
So, the final answer is:
[tex]\[ (x, y, z) = (1, 2, 0) \][/tex]
We hope our answers were helpful. Return anytime for more information and answers to any other questions you may have. Thanks for using our service. We're always here to provide accurate and up-to-date answers to all your queries. Your questions are important to us at Westonci.ca. Visit again for expert answers and reliable information.